Mortality patterns of adolescent and youth in SAARC countries: Findings from the global burden of disease - Sedain, Bhagabati (Nepal Population Journal, 2018)
Adolescence and youth are the healthiest period of life. Despite being a healthy period of life, the people of this age group also suffer significantly higher deaths and disease conditions. This paper analyzes level, trend of all causes mortality and causes of mortality among population aged 10-24 years. Datasets on population aged 10-24 years; number of deaths and cause-specific mortality were obtained from the Global Health Data Exchange platform (GHDx) of the Institute of Health Metrics and Evaluation. This paper utilized broad causes of mortality and the variables: number and death rates for the years 2000, 2005, 2010 and 2015.The estimated number of deaths for aged 10-24 years in SAARC countries is 640,000. About 80% of the deaths occurred in Afghanistan and India. Maldives has the lowest mortality rate. In Bangladesh, India, Nepal and Pakistan, the combination of injuries and non-communicable diseases are the major causes of deaths whereas in Afghanistan, Maldives and Sri Lanka, injuries. Majority of female population in all countries died from communicable, maternal, neonatal, causes. In addition to those causes, natural disaster, war also significantly attributed to adolescent and youth mortality in SAARC region. Overall SAARC region data shows that adolescent and youth death rate has declined between 2000 and 2015. There should be regional priorities for the prevention of adolescent and youth deaths recognizing these causes of deaths. Since these findings are based on GBD estimates, there is an urgent need for new evidence based research to examine the validity.